2013
DOI: 10.17017/j.fish.73
|View full text |Cite
|
Sign up to set email alerts
|

Production and quality assessment of fish burger from the grass carp, Ctenopharyngodon idella (Cuvier and Valenciennes, 1844)

Abstract: Fish burger was produced from grass carp (Ctenophygodon idella) to assess the feasibility of value addition to this low priced fish in Bangladesh. Different food additives (25% mashed potato, 2% NaCl, 2% soybean oil, 2% spices and 0.6% sugar) were used to enhance the consumer’s acceptance of the fishery product. Consumers' acceptance of the fish burger was determined by sensory evaluation based on its color, flavor, softness or firmness (S/F), chewy/rubbery (C/R) using 10 point scoring system by a group of 10 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…The total phenolic compounds were71. Sensory evaluation depends on the product's general acceptability and organoleptic qualities like color, texture and odor (Haq et al 2013). The acquired results (Table,6) demonstrated that the highest level of the sensory quality (color, odor and texture) was obtained in minced chicken meat samples supplied with 2% Nigella sativa seeds extract, followed by 1.5% Nigella sativa seeds extract and still acceptable for more than 6 th days storage.…”
Section: Resultsmentioning
confidence: 99%
“…The total phenolic compounds were71. Sensory evaluation depends on the product's general acceptability and organoleptic qualities like color, texture and odor (Haq et al 2013). The acquired results (Table,6) demonstrated that the highest level of the sensory quality (color, odor and texture) was obtained in minced chicken meat samples supplied with 2% Nigella sativa seeds extract, followed by 1.5% Nigella sativa seeds extract and still acceptable for more than 6 th days storage.…”
Section: Resultsmentioning
confidence: 99%
“…Sensory evaluation is quick, efficient and easy method for getting an idea about acceptance and quality of the product. it depends on organoleptic characteristics as color, texture and product acceptability (Shaltout [52][53][54]). Table 1 revealed that sensory evaluation of treated samples was improved and extended shelf-life during chilling at 1 to 4˚C.…”
Section: Discussionmentioning
confidence: 99%